We Really Need to Talk About Session Tickets: A Large-Scale Analysis of Cryptographic Dangers with TLS Session Tickets - Hebrok, Sven Niclas; Nachtigall, Simon; Maehren, Marcel; Erinola, Nurullah; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (32nd USENIX Security Symposium)

Weisheit und moralischer Intellektualismus im Koran aus intertextueller Perspektive - Dorogova, Elizaveta (Hermeneutiken der Weisheit)

Overcoming Diffusion Limitation of Faradaic Processes: Property‐Performance Relationships of 2D Conductive Metal‐Organic Framework Cu3(HHTP)2 for Reversible Lithium‐Ion Storage - Wrogemann, Jens Matthies; Lüther, Marco Joes; Bärmann, Peer; Lounasvuori, Mailis; Javed, Ali; Tiemann, Michael; Golnak, Ronny; Xiao, Jie; Petit, Tristan; Placke, Tobias; Winter, Martin (Angewandte Chemie International Edition)
Faradaic reactions including charge transfer are often accompanied with diffusion limitation inside the bulk. Conductive two-dimensional frameworks (2D MOFs) with a fast ion transport can combine both - charge transfer and fast diffusion inside their porous structure. To study remaining diffusion limitations caused by particle morphology, different synthesis routes of Cu-2,3,6,7,10,11-hexahydroxytriphenylene (Cu3(HHTP)2), a copper-based 2D MOF, are used to obtain flake- and rod-like MOF particles. Both morphologies are systematically characterized and evaluated for redox-active Li+ ion storage. The redox mechanism is investigated by means of X-ray absorption spectroscopy, FTIR spectroscopy and in situ XRD. Both types are compared regarding kinetic properties for Li+ ion storage via cyclic voltammetry and impedance spectroscopy. A significant influence of particle morphology for 2D MOFs on kinetic aspects of electrochemical Li+ ion storage can be observed. This study opens the path for optimization of redox active porous structures to overcome diffusion limitations of Faradaic processes.
Keywords: General Chemistry; Catalysis

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics

Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation - Zuo, Ruixin; Song, Xiaohong; Ben, Shuai; Meier, Torsten; Yang, Weifeng (Physical Review Research)
Keywords: General Physics and Astronomy

Manipulation of nonautonomous nonlinear wave solutions of the generalized coupled Gross–Pitaevskii equations with spin–orbit interaction and weak Raman couplings - Belobo, D. Belobo; Meier, Torsten (Results in Physics)
Keywords: General Physics and Astronomy

Dynamics of Tradition: Islamic Law and Theology in Relation

Teaching Technologies: Continuous Interplay Between Educational and Industrial Advances - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Teacher Education in the Wake of Covid-19)
The field of teaching technologies is in constant interplay between educational and industrial advances. Since the beginning of the twenty-first century, digitalization and automatization have become increasingly important. In industrial and social life, we see similar fast-moving developments. These factors challenge education, specifically vocational education, greatly, and raise two very different, yet very much connected questions: how to prepare students for their vocational lives and how to prepare teachers to communicate the necessary competencies to their students? This chapter provides an overview of advances, challenges, and possible solutions, focusing on the three key fields of vocational education in Germany: Industry 4.0, Education 4.0, and innovative teacher education. Most importantly, however, the text examines the continuous interplay between and among these fields. The beginning of the chapter is dedicated to vocational teacher education, in accordance with industrial and educational advances. Specifying this, characteristics of Industry 4.0, as well as students' and teachers' perceptions of Industry 4.0, are discussed. This is followed by an introduction to the concept of so-called learning factories as a possible way of integrating aspects of Industry 4.0 in German vocational schools. The end of the chapter is dedicated to the required changes in educational settings today and in the future. Though Industry 4.0, Education 4.0, and innovative teacher education are each widely discussed in the current literature, the interplay of all three fields reveals a research gap. This chapter tries to close this gap and provide an important contribution to the research field.

On Welding of High-Strength Steels Using Laser Beam Welding and Resistance Spot Weld Bonding with Emphasis on Seam Leak Tightness - Schmolke, Tobias; Brunner-Schwer, Christian; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing and Materials Processing)

Screencasting: Documenting Processuality - Eckel, Julia (Screen-Images. Screenshot, Screencast, In-Game Photography)

Inklusiver Mathematikunterricht. Mathematiklernen in Vielfalt von Kompetenzen, Wegen und Lernsituationen - Häsel-Weide, Uta (Die Grundschulzeitschrift)

Addition und Subtraktion verstehen - Graf, Lara Marie; Wienhues, Inga; Häsel-Weide, Uta (Die Grundschulzeitschrift)

The Virus Is Present, Presence Is Virulent: Being Co(m)present With Others in Times of Corona - Eckel, Julia; Linseisen, Elisa (Epidemics and Othering. The Biopolitics of COVID-19 in Historical and Cultural Perspectives)

Navigationen: Tech | Demo (Navigationen - Zeitschrift für Medien- und Kulturwissenschaften)
Keywords: tech demo; technology demonstration; demo or die

Derivation of third order Runge–Kutta methods (ELDIRK) by embedding of lower order implicit time integration schemes for local and global error estimation - Mahnken, Rolf (Computational Mechanics)
Abstract Three prominent low order implicit time integration schemes are the first order implicit Euler-method, the second order trapezoidal rule and the second order Ellsiepen method. Its advantages are stability and comparatively low computational cost, however, they require the solution of a nonlinear system of equations. This paper presents a general approach for the construction of third order Runge–Kutta methods by embedding the above mentioned implicit schemes into the class of ELDIRK-methods. These will be defined to have an Explicit Last stage in the general Butcher array of Diagonal Implicit Runge–Kutta (DIRK) methods, with the consequence, that no additional system of equations must be solved. The main results—valid also for non-linear ordinary differential equations—are as follows: Two extra function calculations are required in order to embed the implicit Euler-method and one extra function calculation is required for the trapezoidal-rule and the Ellsiepen method, in order to obtain the third order properties, respectively. Two numerical examples are concerned with a parachute with viscous damping and a two-dimensional laser beam simulation. Here, we verify the higher order convergence behaviours of the proposed new ELDIRK-methods, and its successful performances for asymptotically exact global error estimation of so-called reversed embedded RK-method are shown.
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

PSΦ: Entwicklung von Unterstützungsmaßnahmen für Theoretische Physik - Abbas, Nilab; Bauer, Anna Brigitte; Reinhold, Peter (Lernen, Lehren und Forschen in einer digital geprägten Welt)

PSФ: Entwicklung einer abgestimmten Studieneingangsphase (Physik) - Bauer, Anna Brigitte; Reinhold, Peter (Lernen, Lehren und Forschen in einer digital geprägten Welt)

Generalised tanh-shaped hyperbolic potential: Klein-Gordon equation's bound state solution - Badalov, Vatan; Badalov, Sabuhi (Communications in Theoretical Physics)
Abstract The development of potential theory heightens the understanding of fundamental interactions in quantum systems. In this paper, the bound state solution of the modified radial Klein-Gordon equation is presented for generalised tanh-shaped hyperbolic potential from the Nikiforov-Uvarov method. The resulting energy eigenvalues and corresponding radial wave functions are expressed in terms of the Jacobi polynomials for arbitrary $l$ states. It is also demonstrated that energy eigenvalues strongly correlate with potential parameters for quantum states. Considering particular cases, the generalised tanh-shaped hyperbolic potential and its derived energy eigenvalues exhibit good agreement with the reported findings. Furthermore, the rovibrational energies are calculated for three representative diatomic molecules, namely $\rm{H_{2}}$, $\rm{HCl}$ and $\rm{O_{2}}$. The lowest excitation energies are in perfect agreement with experimental results. Overall, the potential model is displayed to be a viable candidate for concurrently prescribing numerous quantum systems.
Keywords: Physics and Astronomy (miscellaneous)

Diquat Based Dyes: A New Class of Photoredox Catalysts and Their Use in Aerobic Thiocyanation - Meier, Armin; Badalov, Sabuhi; Biktagirov, Timur; Schmidt, Wolf Gero; Wilhelm, René (Chemistry – A European Journal)
A series of new organic donor–π–acceptor dyes incorporating a diquat moiety as a novel electron-acceptor unit have been synthesized and characterized. The analytical data were supported by DFT calculations. These dyes were explored in the aerobic thiocyanation of indoles and pyrroles. Here they showed a high photocatalytic activity under visible light, giving isolated yields of up to 97 %. In addition, the photocatalytic activity of standalone diquat and methyl viologen through formation of an electron donor acceptor complex is presented.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Rutile, anatase, brookite and titania thin film from Hubbard corrected and hybrid DFT - Badalov, Sabuhi; Bocchini, Adriana; Wilhelm, Rene; Kozub, A. L.; Gerstmann, Uwe; Schmidt, Wolf Gero (Materials Research Express)
As a benchmark, the structural, electronic and optical properties of the three main phases of TiO$\rm{_2}$ crystals have been calculated using Hubbard U correction and hybrid functional methods in density-functional theory. These calculations are compared concerning the available experimental observations on pristine TiO$\rm{_2}$ crystals. Modified hybrid functionals, particularly the PBE0 functional with 11.4% fraction of exact exchange, are shown to provide highly accurate atomic structures and also accurate electronic structure data, including optical excitation energies. With $\rm{DFT+U}$, accurate optical spectra are also possible, but only if the Hubbard U is applied on the O $\rm2p$ electrons exclusively. Furthermore, both methods, the 11.4%-PBE0 hybrid functional and the $\rm{DFT+U_p}$ scheme have been used to study TiO$\rm{_2}$ amorphous ultra-thin films, confirming the agreement of the two methods even with respect to small details of the optical spectra. Our results show that the proposed $\rm{DFT+U_p}$ methodology is computationally efficient, but still accurate. It can be applied to well-ordered TiO$\rm{_2}$ polymorphs as well as to amorphous TiO$\rm{_2}$ and will allow for the calculations of complex titania-based structures.